The relationship between motivation of social viewing experiences, satisfaction, and loyalty in sports broadcasting - Suh, Y.; Chung, T.; Kim, J. (International Journal of Computer Science in Sport, 2019)
The purpose of this study was to examine, within a sports broadcasting setting, the relationship between social viewing users` motivation, satisfaction, and loyalty and to determine if social viewing could be used as a marketing strategy in the sport industry. For this study, data were collected by using an online survey targeting social media users. A total of 379 survey responses were used for the data analysis. The study`s hypothesized model constructs were evaluated using Structural Equation Modeling (SEM) and the data analysis revealed several key findings. The results revealed that the sharing of social viewing experiences in sports broadcasting had a positive impact on user satisfaction. User satisfaction was also positively impacted by both information searching and the excitement found in social sports viewing. Lastly, users` satisfaction positively influenced loyalty.